2008
DOI: 10.2739/kurumemedj.55.13
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Pulmonary Function is Associated with Enhanced Inflammation and Tissue Inhibitor of Metalloproteinase 1 Concentration in the Bronchoalveolar Lavage Fluid of Patients with Lung Parenchymal Sarcoidosis

Abstract: Summary:Lung parenchymal disease is associated with reduced pulmonary function in patients with sarcoidosis, however, the underlying pathophysiology of the condition is unclear. The present study was conducted to characterize the association between pulmonary function and bronchoalveolar lavage (BAL) findings in patients with sarcoidosis. Twenty-three patients with lung parenchymal disease (stage 2) and twenty-five patients without lung parenchymal disease (stage 1) underwent pulmonary function tests, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In Alzheimer’s disease it is a suggested biomarker of ongoing central nervous system inflammation [4]. In respiratory pathology it has been shown that some metalloproteinases are elevated locally in bronchoalveolar lavage fluid of patients with pneumonia, sarcoidosis or adult respiratory distress syndrome [2,3,4]. Other studies have revealed increased concentrations of MMPs, especially MMP-8 and MMP-9, in the sputum of patients with COPD [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Alzheimer’s disease it is a suggested biomarker of ongoing central nervous system inflammation [4]. In respiratory pathology it has been shown that some metalloproteinases are elevated locally in bronchoalveolar lavage fluid of patients with pneumonia, sarcoidosis or adult respiratory distress syndrome [2,3,4]. Other studies have revealed increased concentrations of MMPs, especially MMP-8 and MMP-9, in the sputum of patients with COPD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…They have been implicated in the dissemination of tumors, as matrix metalloproteinase-9 (MMP-9) is capable of releasing the biologically active form of vascular endothelial growth factor, which seems to play a crucial role in the formation of new blood vessels [1,2]. MMP-9 is also involved in the pathogenesis of cardiovascular diseases, taking part in the development and rupture of atherosclerotic plaques, as well as in acute ischemic stroke promoting blood-brain barrier disruption [3]. In Alzheimer’s disease it is a suggested biomarker of ongoing central nervous system inflammation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was also shown that only TIMP-1 correlated significantly with vital capacity of the lung. Capacity of the lung can be infuenced by inflammation (6) and this could be an explanation for significant correlations obtained only between TIMP-1 and inflammatory parameters in our study. However, Piotrowski et al (20) found no significant correlations between neither MMP-9 nor TIMP-1 with lung function parameters.…”
Section: Discussionmentioning
confidence: 63%
“…In the study of Fireman et al (5), it was shown that TIMP-1 was higher in sarcoidosis than in controls, but with marginal significance. Nevertheless, Shimada et al (6) observed significantly increased concentrations of TIMP-1 in sarcoidosis patients with stage 2 when compared with patients in stage 1. This suggests that more pronounced inflammation occuring in stage 2 may contribute to higher levels of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation